Compassionately Aging: The Lived Experience of Elderly Following the Death of a Spouse - Rahmadewi, Safira Rizqi; Lestari, Sri (Jurnal Psikologi Teori dan Terapan, 2024)
Background: The old age is frequent experiencing the repeated loss of loved ones such as life partners, family members, and peers. The death of a spouse becomes a painful experience and has a bad impact on the psychological condition of the elderly. This research aims to acknowledge the lives of the elderly who experience the death of a spouse and represent the elderly's self-compassion in interpreting their lives. A qualitative approach with a phenomenological design was used in this study. Participants were four elderly over 60 years old who experienced the loss of a partner with a span approximately one year after the death. In-depth interviews with open-ended questions were used when collecting the data. Six themes were obtained within the interviews: preserving social relations, adapting to change, social support, accepting the spouse's death, religiosity, and the meaning of losing a spouse. The findings present that the elderly can cope with the difficult times after their spouse's death owing to social support, faith, and their ability to overcome the difficulties. The elderly show an attitude of acceptance of life changes and gratitude, followed by a positive outlook on future life.